SOSIALISASI PENJUALAN ONLINE DITINJAU DARI HUKUM JUAL BELI ISLAM TERHADAP PEGIAT UMKM - Ismiasih, Novi; Mustika, Tito Nur; Setyowati, Suci Yongki (Mafaza : Jurnal Pengabdian Masyarakat, 2024)
Online buying and selling is a new phenomenon occurring in society. This buying and selling activity uses the Internet without having to meet the seller and buyer in person. With the existence of online buying and selling, it turns out that there are still some people, especially UMKM business actors, who do not know the laws of Islamic online buying and selling. Seeing this problem, the researcher provided socialization about online sales in terms of Islamic buying and selling law. Buying and selling online according to scholars and fatwa institutions justifies buying and selling online but must still pay attention to the legal principles of buying and selling in Islam. This service was carried out on October 28 2023 using the face-to-face method directly to UMKM actors. The results of this service received a good response from the community, especially UMKM business actors. Through this service, UMKM business actors become aware of Islamic laws regarding online buying and selling because this service provides additional insight into knowing the prohibitions and principles of online buying and selling.